The Comparison of Circular Economy Analysis in Developed and Developing Countries - Indriawati, Ratna Malisa; Gravitiani, Evi; Samara, Pramana Widya (Universitas Muhammadiyah Ponorogo, 2024)
This study seeks to present a better understanding of knowledge about the circular economy by referring to literature studies in developed and developing countries during the observation period from 2006 to 2022. This study provides an overview of the bibliometric approach: time analysis, journal analysis, co-authorship analysis, keyword analysis, citation analysis, country analysis, and agency analysis. The level of research contribution in developed and developing countries tended to be low until 2016, increasing significantly in recent years. Keyword analysis reveals that Circular Economy has the highest contribution in 2019 for developed countries and in 2020 for developing countries. Then, the citation analysis shows that